METHODOLOGICAL CONSTRUCTION OF THE MECHANISM OF STATE SUPPORT FOR EXPORTS THROUGH SUBSIDIZING - Islamov Erkin Gayratovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article attempts to highlight the reasons for the increasing importance of improving the support system, the positive impact of exports on economic growth in our country, as well as its new aspects. The features and tasks of applying its effective tools and methods are described on the basis of mastering the world practice of an effective foreign trade operation and the experience of modern trends in the export promotion mechanism. The directions of supporting the positive impact of effective exports on economic growth in the prospects for the socio-economic development of the Republic of Uzbekistan until 2030 are substantiated.